2022
DOI: 10.3390/app12104869
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Meteorite Surfaces Ablated by High-Power Lasers: Review and Applications

Abstract: Under controlled laboratory conditions, lasers represent a source of energy with well-defined parameters suitable for mimicking phenomena such as ablation, disintegration, and plasma formation processes that take place during the hypervelocity atmospheric entry of meteoroids. Furthermore, lasers have also been proposed for employment in future space exploration and planetary defense in a wide range of potential applications. This highlights the importance of an experimental investigation of lasers’ interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…shock expansion of material released from the solid meteorite target (Křivková et al, 2022). The atmospheric entry of a meteoroid does not only result into its sputtering, its fragmentation or ablation (Rogers et al, 2005;Popova, 2006;Vondrak et al, 2008;Silber et al, 2018), or even to meteorite or asteroid impact, if the body is big enough or cohesive (Collins et al, 2005), but also to the random explosion event that has been observed many times for smaller bodies and which are well-known from the case of the Tunguska event in 1908 (Napier and Asher, 2009).…”
Section: Simulation Of Meteoroid Disintegrationmentioning
confidence: 99%
See 1 more Smart Citation
“…shock expansion of material released from the solid meteorite target (Křivková et al, 2022). The atmospheric entry of a meteoroid does not only result into its sputtering, its fragmentation or ablation (Rogers et al, 2005;Popova, 2006;Vondrak et al, 2008;Silber et al, 2018), or even to meteorite or asteroid impact, if the body is big enough or cohesive (Collins et al, 2005), but also to the random explosion event that has been observed many times for smaller bodies and which are well-known from the case of the Tunguska event in 1908 (Napier and Asher, 2009).…”
Section: Simulation Of Meteoroid Disintegrationmentioning
confidence: 99%
“…In the first part, this review summarizes contemporary experimental approaches to studying meteor and impact plasma physics and chemistry. The second part of this paper focuses on recent developments in the application of high power lasers to spaceborne observations of meteors in the Earth's atmosphere (Ferus et al, 2019;Czech Ministry of Transportation, 2021), detection of impacts and atmospheric reprocessing on exoplanets (Ferus et al, 2019;Navarro-González et al, 2019;Navarro et al, 2020;Ferus et al, 2021), space weathering and meteoroid ablative disintegration during atmospheric entry (Kaluna et al, 2017;Křivková et al, 2022).…”
Section: Introductionmentioning
confidence: 99%